IMPLEMENTASI METODE DESIGN THINKING PADA PERANCANGAN APLIKASI GAME EDUKASI PENCEGAHAN KEKERASAN SEKSUAL ANAK BERBASIS MULTIMEDIA - Siregar, Tara Naura (UNIVERSITAS STEKOM, 2024)
This research aims to serve as a useful supportive tool in providing knowledge to children about early sexual education to prevent sexual violence using interactive multimedia as an alternative solution for providing sex education to children. The sample for this research consists of fourth-grade students at SD Negeri Percobaan Medan. Through the Design Thinking approach, this research resulted in an educational android game application named